Assessing factors influencing pharmacy interns career choices in Saudi Arabia - Douha Bannan; Mohannad Alshibani; Samah Alshehri; Ahmed Aljabri; Hussam Kutbi (Elsevier, 2021)
Background: The number of students enrolled in the colleges of pharmacy in Saudi Arabia is high, and the number of pharmacy graduates expected to join the workforce in the coming years is expected to grow. There are limited number of studies that assess factors influencing pharmacy students' career choices in Saudi Arabia in the literature. The aim of this study was to assess the factors that influence career goals and to investigate students' perceptions about their career goals. Methods: This study was a prospective cross-sectional survey targeting PharmD students in their last year (i.e. interns) in the academic year of 2018 - 2019. A questionnaire containing four parts and total questions of 32 was completed by interns. Data collected and analyzed using Qualtrics. This study was reviewed and approved by the Unit of Biomedical Ethics Research Committee at King Abdulaziz University. Results: 93 were reachable via email and all of them attended the interview and completed the survey (100% response rate). The most important job considerations were: work environment (67.7%), advancement opportunities (55.9%), salary (52.7%), benefits (40.9%), flexible work schedule (34%), and finally geographic region (29%). The top ranked career goal upon graduation were in industry and drug company (35.5%), clinical pharmacy (26.9%), (14%) academics/research and hospital pharmacy setting (inpatient/outpatient) (14%) each, and regulatory and community pharmacy (3.2% and 4.3%, respectively) Conclusion: This study showed that work environment, advancement opportunities, and salary were the most important job consideration for pharmacy interns. The top ranked career goals were industry and drug company followed by clinical pharmacy. Further studies across Saudi Arabia are needed to confirm our results.